2006
DOI: 10.1507/endocrj.53.209
|View full text |Cite
|
Sign up to set email alerts
|

Normal Delivery Following an Uneventful Pregnancy in a Japanese Acromegalic Patient after Discontinuation of Octreotide Long Acting Release Formulation at an Early Phase of Pregnancy

Abstract: Abstract. We report a 35-year-old woman with active acromegaly despite pituitary surgery and irradiation who received continuous octreotide LAR treatment for the control of GH excess until discovery of her pregnancy. The patient delivered a healthy boy following an uneventful pregnancy after discontinuing octreotide LAR as soon as possible at the early phase of pregnancy. Despite a substantial maternal-fetal transfer of octreotide, postnatal development was normal at 3 years of age. In almost all previously de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
1
22
0
2
Order By: Relevance
“…GH levels were stable but IGF-1 levels were significantly elevated after delivery. Similar cases of suppressed GH and/or IGF-1 during pregnancy have recently been reported by other investigators [5][6][7][8][9], and some patients showed clinical and biochemical improvement during pregnancy [8]. These data suggest that GH secretion in pregnant acromegalic patients may not be entirely autonomous and may be associated with a degree of negative feedback control that could be exerted by a circulating factor of placental origin, probably human placental lactogen or placental GH variant.…”
Section: Discussionsupporting
confidence: 84%
“…GH levels were stable but IGF-1 levels were significantly elevated after delivery. Similar cases of suppressed GH and/or IGF-1 during pregnancy have recently been reported by other investigators [5][6][7][8][9], and some patients showed clinical and biochemical improvement during pregnancy [8]. These data suggest that GH secretion in pregnant acromegalic patients may not be entirely autonomous and may be associated with a degree of negative feedback control that could be exerted by a circulating factor of placental origin, probably human placental lactogen or placental GH variant.…”
Section: Discussionsupporting
confidence: 84%
“…Newborns from women who interrupted medical treatment before or at the beginning of pregnancy have been typically normal (2,3,4,5,38). Also, children born from women with acromegaly who discontinued treatment during pregnancy have been shown to have normal general health status at 2, 3 and 6 years of age (73,74,75), as well as IQ scores similar to those born from normal women or from women with prolactinoma (76). However, as some patients with acromegaly may have or develop impaired glucose tolerance/diabetes mellitus and hypertension during pregnancy, their newborns should also be considered at a higher risk for macrosomia and microsomia (77) respectively.…”
Section: Effect Of Acromegaly and Its Treatment On Fetal Developmentmentioning
confidence: 99%
“…Although octreotide crosses placental barrier and placenta has somatostatin receptors that bind octreotide (78), no serious adverse fetal outcomes have been detected in nearly 50 (2,3,4,5,7,36,38,47,48,50,51,55,57,63,79,80,81,82,83,84) cases of transient exposure (mostly in first trimester) nor in a much smaller number of continuous exposure to somatostatin analogs (SA) and/or dopaminergic agonists (4,64,73,75,78,85,86,87). Notwithstanding, concerns about low birth weight associated to fetal exposure to SA either alone or, as more often reported, in combination with dopaminergic agonists (DA) have been raised by a large retrospective study and by few case reports (3,4,85,88).…”
Section: Effect Of Acromegaly and Its Treatment On Fetal Developmentmentioning
confidence: 99%
“…Although SA, octreotide, and lanreotide are more efficacious than DA for the treatment of acromegaly, these agents have not been commonly used during pregnancy (4). Uneventful pregnancies have been reported in which SA was continued during the pregnancy without any side effects (13,20,21). Besides, medical treatment with SA during pregnancy was associated with low birth weight.…”
Section: Discussionmentioning
confidence: 99%